Disclosure of Occupational Safety and Health in Sustainability Reports - Veronika Saptarini; Victoria Ari Palma Akadiati (International Journal of Economics, Management and Accounting, 2026)
This study was prompted by the stark contradiction between the rise in national workplace accident rates from 2016 to 2024 and the largely superficial nature of corporate sustainability reports. This phenomenon of safety washing creates an urgent need to re-evaluate the integrity of OSH reporting in Indonesia. This study aims to analyze the transformation of OSH disclosure from mere administrative transparency toward genuine accountability, as well as its impact on employee engagement. The study employs an integrative literature review method, conducting a systematic synthesis of 20 key studies from the period 2010–2026. Unlike previous studies that focused on market performance, this research offers novelty through an integrative model that links accounting reporting aspects with organizational psychological impacts through the lens of the latest 2026 regulations. Findings indicate that OSH transparency supported by strong governance can foster substantive accountability. Honest disclosure has proven to be a positive signal that enhances employee trust and emotional engagement. The integration of transparency and accountability in OSH reporting is a strategic key to building a safety culture and human resource loyalty.